FROM LYRICS TO LEARNING: THE EFFECT OF SONGS ON STUDENTS' MOTIVATION TO LEARN ENGLISH - Sholihah, Ayu Ni’matus; Hossain, Rumana; Farid, Achmad; Yusuf, Adi (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2024)
The research aims to investigate the impact of popular English songs on students' motivation to learn English at School X in Jombang using a quasi-experimental design. This study focuses on implementing English popular songs (EPS) popular in the last 15 years and remain popular today. A sample of 42 students from two different classes participated in the study. Data were gathered using a questionnaire and analyzed statistically with SPSS version 20. The findings indicate that students' motivation to learn English was moderate, based on their responses to the Likert scale questionnaire. Furthermore, Spearman's rank correlation test found a moderate correlation between students' motivation and the use of EPS. In light of these findings, using EPS does not significantly affect students' motivation. However, it was noted that students' learning experiences, a component of the L2 Motivational Self System, improved. Additionally, a Chi-square test of independence examined the relationship between the frequency of students listening to EPS and their motivation. The results suggest that students who frequently listen to English songs tend to have higher motivation. This study provides insights into the potential benefits of incorporating popular music into English language learning to enhance student engagement and motivation.